The Modification of Perfectionism Questionnaire by N. Garanyan, A. Kholmogorova - Zavada, Tetiana (Psychological Prospects Journal, 2015)
This article describes the procedure of adaptation and modification of Ukrainian-language version of the perfectionism questionnaire by N.Garanyan, A. Kholmogorova. The technique, developed by Russian scientists, allows to measure the components that make up the structure of perfectionism, and are related to: 1) too high claims and standards of expected results of activity; 2) violation of social cognitions (high expectations to surrounded people); 3) personalization, providing constant comparing oneself with others; 4) polarized thinking on binary principle of performance assessment and planning (“all or nothing”); 5) the selection of negative information on the results of one’s own activity. The article also describes two aspects that are important in the structure of perfectionism: “self-blame” and “dependence on the position of environment”, which, subsequently, were included in the perfectionism questionnaire by N. Garanyan and A.Kholmohorova. Authors’ questions to the two scales contain 15 statements, 8 of which relate to the scale of “self-blame” and 7 – “dependence on the positions of environment”. The highly statistically significant reliability is proved (indexes factor α-Cronbach) modified questionnaire, including a general indicator of perfectionism and all its scales (components). The results of the factor analysis indicate that two scales attached to the questionnaire expand the structure of perfectionism. Using cluster analysis, we distinguished three levels of perfectionism: high, medium and low. Statistical significance of modified questionnaire scales is also confirmed by the results of discriminant analysis.